Pengaruh Supervisi Kepala Sekolah dan Musyawarah Guru Mata Pelajaran (MGMP) Terhadap Kepuasan Kerja Guru di Mts Darunnajah Jakarta - Hanna, Annisa Farhana; Rokimin; Samiyono (STIT Fatahillah, 2024)
Teacher job satisfaction is one of the factors that must be considered, if teachers feel satisfied at work, it will create an atmosphere full of togetherness, have the same responsibilities, a good communication climate, and also high morale so that school goals can be achieved optimally. But on the other hand, if teachers do not feel satisfied, it will create an atmosphere that is rigid, boring, and low team spirit. The method used in this research is a survey method with a quantitative approach and data collection techniques using a questionnaire or questionnaire distributed to 66 teachers at MTs Darunnajah Jakarta as a sample of this study. From the results of research and calculations, it can be seen that there is a significant influence between principal supervision (X1) on teacher job satisfaction (Y) with a contribution between variables X1 to Y of 59.2%. The influence between subject teacher deliberations (X2) on teacher job satisfaction (Y) amounted to 62.5%. Based on the results of the coefficients of determination X1 and X2 on Y, it is simultaneously obtained at 0,752. This means that there is an influence between X1 and X2 to Y by 75.2% of the regression equation Ý = R2 × 100% or 0.752 × 100% = 75,2% while the remaining 24.8% is influenced by other factors